KARAKTERISASI ZEOLIT ALAM SELONG BELANAK LOMBOK SEBAGAI ADSORBEN DALAM PEMURNIAN ALKOHOL FERMENTASI - Hulyadi Hulyadi (Universitas Pendidikan Mandalika Mataram, 2017)
NTB has a large zeolite potential with a zeolite content percentage of 190,405 tons. One area that has great potential is the Selong belanak Central Lombok precisely at coordinates 8o51'48.5